Association of dietary fatty acid intake with hypertension in children and adolescents: evidence from the NHANES 2005-2018 - Xiumin Li; Fengqin Qi; Zhihong Zhao; Jinbang Ma (Frontiers Media S.A., 2023)
AimThis study aims to evaluate the association between dietary fatty acid intake and hypertension in children and adolescents.MethodsThis cross-sectional study used data of children and adolescents aged 8-17 years from the National Health and Nutrition Examination Survey (NHANES) 2005-2018. Dietary intake of total fat and fatty acid was evaluated via two 24-h dietary recall interviews. Multivariate logistic regression models were used to assess the association between fatty acid intake and hypertension, with odds ratios (ORs) and 95% confidence intervals (CIs) calculated. A subgroup analysis was conducted according to gender, age, and body mass index Z-score.ResultsThis study included 13,330 subjects, of which 11,614 were non-hypertensive and 1,716 were hypertensive. Higher intake of total polyunsaturated fatty acids (PUFAs) was associated with significantly lower odds of hypertension (OR = 0.85, 95% CI: 0.74-0.97, P = 0.018). No significant associations were found between the density of total saturated fatty acid, monounsaturated fatty acids, and PUFAs and the odds of hypertension (all P > 0.05). Increased intake of omega-3 (OR = 0.82, 95% CI: 0.72-0.93, P = 0.002) and omega-6 (OR = 0.86, 95% CI: 0.75-0.98, P = 0.025) PUFAs, octadecatrienoic acid (OR = 0.82, 95% CI: 0.72-0.93, P = 0.003), and octadecadienoic acid (OR = 0.86, 95% CI: 0.75-0.98, P = 0.025) was associated with significantly lower odds of hypertension, and individuals with higher omega-6/omega-3 ratio had significantly higher odds of hypertension (OR = 1.09, 95% CI: 1.02-1.17, P = 0.025). The density of omega-3 PUFAs (OR = 0.86, 95% CI: 0.78-0.95, P = 0.004) and octadecatrienoic acid (OR = 0.87, 95% CI: 0.78-0.96, P = 0.006) was inversely associated with the odds of hypertension, and the omega-6/omega-3 ratio was positively associated with the odds of hypertension (OR = 1.09, 95% CI: 1.02-1.17, P = 0.012).ConclusionTotal PUFA intake was negatively associated with the odds of hypertension in children and adolescents. Higher intake of omega-3 and omega-6 PUFAs, octadecatrienoic acid, and octadecadienoic acid, as well as density of omega-3 PUFAs and octadecatrienoic acid, was associated with lower odds of hypertension.